Filogenetik Ular Sanca Batik (Malayopython reticulatus) Lokal Jawa Berdasar Sekuen Gen Sitokrom B (PHYLOGENETIC STUDY OF RETICULATED PYTHON (MALAYOPYTHON RETICULATUS) JAVAN LOCALITY BASED ON GENE CYTOCHROME B SEQUENCES) - Raharjo, Slamet; Hartati, Sri; Indarjulianto, Soedarmanto; Widayanti, Rini; Nururrozi, Alfarisa (Jurnal Veteriner; Vol 19 No 2 (2018), 2018)
Reticulated python (Malayopython reticulatus) Javan locality has different phenotype among West Java, Central Java and East Java locality. This research aim was to study the phylogenetic of reticulated python (M. reticulatus) Java locality based on the partial gene cytochrome b sequences. Fifteen males and females adult healthy reticulated pythons (5 from West Java, 5 from Central Java and 5 from East Java) were used in this study. As much as 1 mL blood samples collected from ventral coccygeal vein, put in Eppendorf with EDTA then sent to Laboratory of Biochemistry, Faculty of Veterinary Medicine, Gadjah Mada University for total Deoxyrybo Nucleic Acid (DNA) extraction and DNA amplification with Polymerase Chain Reaction (PCR) method. DNA sequencing was done in First Base Company Singapore by PT. Genetika Science Jakarta. The gene cytochrome b sequences were phylogenetically analysed using Neighbor joining (MEGA v. 5.0) method. The length of partial gene cytochrome b nucleotides sequence of M. reticulatus from West Java, Central Java and East Java locality was 819 bp. The phylogram using Neighbor joining method showed that Malayopython reticulatus Central Java locality was differentiated from West Java locality, while the East Java locality was undifferentiated from West Java and Central Java locality, namely in the same group. It could be concluded that reticulated python (M. reticulatus) Java locality has partial gene cytochrome b sequences with 819 bp. The phylogenetic of Malayopython reticulatus West Java and several from East Java were located at same branch with M. reticulatus GenBank, while the Central Java and several from East Java were located at different branch. It needs further research with more samples and validity of localities for better result.
Keywords: filogenetik, Malayopython reticulatus, lokalitas Jawa, Sitokrom B